Instruments to Gauge Emotional Regulation in Children with Disabilities: A Scoping Review - Sari, Anggi Luckita; Haryanti, Fitri; Hartini, Sri (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Children with disabilities have less emotional regulation than children without disabilities, and 62.2% have mental health disorders, leading to high levels of comorbidity. Various instruments to measure emotion regulation in children have been developed, but instruments with adequate validity and reliability have not been reported. One way to gauge emotional regulation is to use a measurement instrument. This study aimed to explore instruments of assessment of emotion regulation in children with disabilities that have adequate validity and reliability. Methods: This scoping review was conducted to explore the instruments measuring the emotional regulation of children with disabilities. The search was conducted through the Google Scholar, PubMed, and Science Direct databases and included articles published between 2016-2021. The selection process was done according to the Preferred Reporting Elements for Systematic Review and Descriptive Analysis (PRISMA) guidelines. The search process used appropriate populations, concepts, and contexts. The critical appraisal used the Joanna Briggs Institute checklist. Results: Out of 22,835 articles, 14 articles were selected for this review. Some instruments can be applied to measure the emotional regulation of children with disabilities, such as ERC, DERS, FEEL-KJ, ERICA, EDI, BRIEF, ERQ, and CERQ. In general, if the instrument has a good internal consistency, then it can be used to measure the emotional regulation of children and teenagers with disabilities aged 4-19 years. Conclusion: All of the identified instruments can be used to measure the emotional regulation of children with disabilities.